Belgian delegation invited by the TUC to attend the congress in St. Andrew's Hall. Place of persons indicated on back. From: archive F. Domela Nieuwenhuis, VI a 1 (B), no.19
Belgian delegation invited by the TUC to attend the congress in St. Andrew's Hall. Place of persons indicated on back. From: archive F. Domela Nieuwenhuis, VI a 1 (B), no.19.